Synthesis and Properties of Doped Barium Titanate with High Dielectric Permittivity - Reshytko, Borys; V'yunov, O. (My University, 2017)
Dielectric and semiconductor BaTiO3 ceramic samples have been synthesized and their electrical and physical properties have been studied. It have been shown that the semiconductor ceramic samples of barium titanate are characterized by a high values of dielectric permittivity, which significantly higher in comparison with dielectric samples due to the formation of additional polarization at the grain boundaries and metal-dielectric transitions.
Keywords: high dielectric permittivity; ferroelectric polarization; interface metal-dielectric; grain boundaries; hopping conduction; висока діелектрична проникність; сегнетоелектрична поляризація; інтерфейс метал-діелектрик; границі зерен; стрибкова провідність; высокая диэлектрическая проницаемость; сегнетоэлектрическая поляризация; интерфейсы металл-диэлектрик; границы зёрен; прыжковая проводимость; кафедра технологічного обладнання та комп’ютерних технологій проектування